Karakteristik Arsitektur Sunda pada Rumah Raden Aria Wangsakara, Kampung Lengkong Kyai - Rahmania Indrianti Yudistira; Muhammar Khamdevi (MARKA (Media Arsitektur dan Kota) : Jurnal Ilmiah Penelitian, 2023)
Raden Aria Wangsakara's house is an architectural heritage object in Kampung Lengkong Kyai in Tangerang. He is a scholar from Sumedang and a prince from the Cirebon Sultanate, who has an important relationship with the history of Banten and Jayakarta in general, and Tangerang and Tigaraksa in particular. At a glance, his house is similar to Betawi houses or like traditional houses on the north coast of Sunda-Banten, which are multicultural in general. What are the characteristics of this house? This study intends to analyze the architectural characteristics of this house using a qualitative approach in the form of a case study. This analysis was carried out to analyze and verify the type of space, type of form, and type of building style. The results of this study indicate the type of space and the type of form that still follows the Sundanese house but is modified in the context of the local physical environment which is close to the Cisadane River and the context of a multicultural environment. The style type of the house borrowed and received some elements of Indo-Islamic, Arabic, and European Colonial styles.